Suffering and Christianity: conversion and ethical change among the Newars of Bhaktapur - Gibson, I; Gellner, D; Sarró, R (2015)
This thesis argues that conversion to Christianity in the Nepali city of Bhaktapur is closely connected with ethical attitudes towards suffering in Bhaktapurian churches. This argument is situated within broader debates in the anthropology of Christianity. Anthropologists have debated the extent to which Christianity is a force for cultural discontinuity, and have often connected it with modernity and individualism. I contribute to these discussions by showing how distinctively Christian conceptions of suffering may promote cultural change by stimulating new understandings of selfhood and ethics. The first three chapters explore the social life of Bhaktapur’s Hindu majority. I describe how the last fifty years have seen a process of cultural unsettlement in Bhaktapur; one aspect of this unsettlement has been a disruption of traditional norms of care and deference. It is in this context that the distinctive ethics of Christianity have proved attractive to some. Those who convert have typically experienced a significant episode of suffering, and have felt themselves to be failed by those around them. They find in churches a framework that emphasises the moral significance of inner experience (I call this ‘inwardness’) and addresses affliction more in terms of ethics than ritual. I describe these ethics in terms of ‘care’: they stress presence with the afflicted person, engagement with their experience, and appeal to God in prayer. After two chapters describing Christianity in Nepal and Bhaktapur in general terms, I devote four chapters to examining different categories of Bhaktapurian Christians: those who have experienced healing, women, leaders, and youth. I focus on four conversion narratives, and relate these narratives both to other ethnographic materials and to broader trends in Bhaktapurian and global Christianity. I highlight the significance of the values of inwardness and care, and of narrative itself, in the life-worlds of Bhaktapurian Christians.